2020
DOI: 10.1002/joc.6519
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint influences of eastern Pacific El Niño–southern oscillation and quasi‐biennial oscillation on Northern Hemispheric stratospheric ozone

Abstract: Using ozone observations, reanalysis data, and climate model simulations, this study investigates in detail the independent and joint influences of the eastern Pacific (EP) El Niño-Southern Oscillation (ENSO) and the quasi-biennial oscillation (QBO) on stratospheric ozone in the Northern Hemisphere (NH) during winter. Statistically, the stratospheric ozone in the NH in winter increases during El Niño events but decreases during La Niña events. Stratospheric ozone increases in the east wind phases of the QBO (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 117 publications
(190 reference statements)
1
13
0
Order By: Relevance
“…Naoe et al, (2017) , Zhang et al, (2021)). Indeed, Xie et al, (2020) showed linear interactions between the QBO and EP El Niño signals, and its interactions in the extratropics during El Niño events were evaluated in Calvo et al, (2009). In our study, we have eliminated its influence performing a multiple linear regression analysis.…”
Section: Figure 3 October To March Composite Evolution Of Ozone Mixin...mentioning
confidence: 99%
“…Naoe et al, (2017) , Zhang et al, (2021)). Indeed, Xie et al, (2020) showed linear interactions between the QBO and EP El Niño signals, and its interactions in the extratropics during El Niño events were evaluated in Calvo et al, (2009). In our study, we have eliminated its influence performing a multiple linear regression analysis.…”
Section: Figure 3 October To March Composite Evolution Of Ozone Mixin...mentioning
confidence: 99%
“…Figure 1 suggests that the time series of HCl anomalies is mainly characterized by interannual variability, which may be caused by factors with interannual variations; e.g., the El Niño-Southern Oscillation (ENSO), the Quasi-Biennial Oscillation (QBO), and Stratospheric Sudden Warming (SSW). SSW, El Niño, and the east phase of the QBO (EQBO) generally correspond to strong tropospheric wave activity and a weaker polar vortex, while La Niña and the west phase of the QBO (WQBO) correspond to weaker tropospheric wave activity and a stronger polar vortex (Taguchi and Hartmann, 2006;Wei et al, 2007;Garfinkel and Hartmann, 2008;Calvo and Garcia, 2009;Chen and Wei, 2009;Xie et al, 2012Xie et al, , 2020Richter et al, 2015;Zhang et al, 2015). In addition, warming of the North Pacific SST (SST NP ) is also associated with weak tropospheric wave activity and a stronger polar vortex (Hurwitz et al (2011)).…”
Section: R1 (Control Run)mentioning
confidence: 99%
“…Therefore, processes like the El Niño-Southern Oscillation (ENSO) and the quasi-biennial oscillation (QBO), which have important influences on the interannual variations in the stratospheric circulations, affect the stratospheric ozone significantly (e.g. Lee et al, 2010;Xie et al, 2014;Lu et al, 2019;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The influences of QBO, which are the dominant mode of interannual variability in the equatorial stratosphere (Baldwin et al, 2001), on ozone have been investigated by lots of studies (e.g. Randel and Wu, 1996;Lu et al, 2019;Xie et al, 2020;Zhang et al, 2021). QBO appears as alternating easterly and westerly winds that propagate down from the top (∼ 50 km) to the bottom (∼ 16 km) of the stratosphere, with a period of about 28 months (Baldwin et al, 2001;Anstey and Shepherd, 2014;Coy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%